ATM/NEMO signaling modulates the expression of PD-L1 following docetaxel chemotherapy in prostate cancer. Issue 7 (22nd July 2021) - Wang, Zongren; Zhang, Xueling; Li, Wuguo; Su, Qiao; Huang, Zhaoyang; Zhang, Xinyao; Chen, Haiqi; Mo, Chengqiang; Huang, Bin; Ou, Wei; Chen, Junxing; Zhao, Guangyin; et al.
Abstract : Background: The efficacy of docetaxel-based chemotherapy is limited by the development of drug resistance. Recent studies demonstrated the efficacy of anti-programmed death-1 (PD-1)/programmed cell death ligand-1 (PD-L1) immunotherapies in metastatic prostate cancer. The ataxia telangiectasia mutation (ATM) protein plays a crucial role in maintaining genome stability and function of mitosis. Here, we aimed to determine whether PD-1/PD-L1 signaling contributes to the resistance to DTX and to elucidate the mechanism underlying DTX-induced PD-L1 expression. Methods: In this retrospective study, PD-L1 expression was analyzed in 33 tumor tissue samples from prostate cancer patients. Prostate cell lines were used to perform functional assays and examine underlying mechanisms in vitro. A fully mouse prostate cancer model and a humanized chimeric mouse bearing human prostate tumors and peripheral blood mononuclear cells were used for in vivo assays. Results: We have shown that DTX, a chemotherapeutic drug which causing microtubule interference, could significantly induce the expression of PD-L1 in prostate cancer cells. This effect is blocked by the inhibition of ATM, suggesting that it plays an essential role in PD-L1 expression upregulated by DTX. Mechanistic studies have shown that ATM activity in cancer cells enhances the stability of the NF-κB essential modulator (NEMO), which leading to an increase in the NF-κB activity and PD-L1 expression. Using the mouse model, it was further demonstrated that a combination of ATM and NEMO inhibitors along with DTX augmented the antitumor efficacy of chemotherapy, which are comparable to that of PD-L1 antibody. Conclusions: Our findings have revealed that a previously unrecognized ATM-NEMO signaling which induced by DTX is capable of suppressing tumor immunity by activating the expression of PD-L1, suggesting that the ATM-NEMO-NF-κB axis can be exploited to restore the immune balance and overcome cancer resistance triggered by DTX. Graphic Abstract : supplementary file 1